Phloroglucinol Treatment Induces Transgenerational Epigenetic Inherited Resistance Against Vibrio Infections and Thermal Stress in a Brine Shrimp (Artemia franciscana) Model - Roy, Suvra; Kumar, Vikash; Bossier, Peter; Norouzitallab, Parisa; Vanrompay, Daisy (Frontiers in Immunology, 2019)
Emerging, infectious diseases in shrimp like acute hepatopancreatic necrosis disease (AHPND) caused by Vibrio parahaemolyticus and mortality caused by other Vibrio species such as Vibrio harveyi are worldwide related to huge economic losses in industrial shrimp production. As a strategy to prevent disease outbreaks, a plant-based phenolic compound could be used as biocontrol agent. Here, using the brine shrimp (Artemia franciscana) as a model system, we showed that phloroglucinol treatment of the parental animals at early life stages resulted in transgenerational inherited increased resistance in their progeny against biotic stress, i.e. bacteria (V. parahaemolyticus AHPND strain and V. harveyi) and abiotic stress i.e. lethal heat shock. Increased resistance was recorded in 3 subsequent generations. Innate immune-related gene expression profiles and potential epigenetic mechanisms were studied to discover the underlying protective mechanisms. Our results showed that phloroglucinol treatment of the brine shrimp parents significantly (p<0.05) enhanced the expression of a core set of innate immune genes (DSCAM, proPO, PXN, HSP90, HSP70, LGBP) in subsequent generations. We also demonstrated that epigenetic mechanisms such as DNA methylation, m6A RNA methylation and histone acetylation and methylation (active chromatin marker i.e. H3K4Me3, H3K4me1, H3K27me1, H3 hyperacetylation, H3K14ac and repression marker i.e. H3K27me3, H4 hypoacetylation) might play a role in regulation of gene expression leading towards the observed transgenerational inheritance of the resistant brine shrimp progenies. To our knowledge, this is the first report on transgenerational inheritance of a compound induced robust protected phenotype in brine shrimp, particularly protected against AHPND caused by V. parahaemolyticus and vibriosis caused by V. harveyi. Results showed that epigenetic reprogramming is most likely to play a role in the underlying mechanism.